HONGOS Y ALGAS ASOCIADAS A MANCHAS FOLIARES EN ESPECIES FORESTALES EN EL CAMPUS DE LA UNIVERSIDAD NACIONAL DE ASUNCIÓN, PARAGUAY - Díaz Lezcano, Maura (2024)
Phytopathogenic fungi are the main limitations in the development and productivity of forest species. The objective of this research was to identify the phytopathogenic microorganisms associated with leaf spots of forest species located on the premises of the Faculty of Agrarian Sciences of the National University of Asunción, Paraguay. Individuals of each species that present leaves with initial symptoms were randomly selected, collecting two leaves for each symptom and placing them in airtight bags. For the isolation and identification of fungi, the samples obtained were processed in the following ways: direct and indirect assembly (sowing in Potato Dextrose Agar culture medium). The phytopathogenic fungi were identified thanks to their morphological characters such as: colony texture and coloration, somatic structures and spores. Some phytopathogenic species have been identified: Powdery mildew in Handroanthus hepthaphyllus, Algal spot - Cephaleuros virescens Kunze in Eugenia uniflora, Rust in Handroanthus impetiginosus - Prospodium bicolor, Tar spot - Apiosphaeria guaranitica in Handroanthus albus, Coleosporium plumeriae rust in Plumeria rubra and Phyllachora balansa and in Cedrela fissilis. It is concluded that with the identification of phytopathogenic microorganisms associated with native forest species there is the opportunity to detect sources of infection and thereby establish sanitary actions for a future management program.